3D-printed patient-specific guides improve screw accuracy in upper cervical spine surgery: a comparative study - Guoqi Niu; Yalong Guo; Gong Zhou; Yang Gao; Weili Jiang; Hui Chen; Hu Nie; Tao Liu; Zheng Sun; Jiawei Cheng; Yi Yang; Jianzhong Bai (Frontiers in Neurology, 2026)
Objective To evaluate the feasibility and clinical efficacy of patient-specific 3D-printed guide plates for pedicle screw placement in the upper cervical spine, compared with the conventional free-hand technique. Methods A retrospective analysis was conducted on 39 patients who underwent upper cervical spine surgery between June 2009 and June 2022. Patients were divided into a guide plate group ( n = 24) and a free-hand control group ( n = 15). Surgical parameters (operative time, blood loss, fluoroscopy frequency), screw placement accuracy (assessed by Kawaguchi classification on postoperative CT), and clinical outcomes (VAS, JOA, and ASIA scores) were compared between groups. Results A total of 141 pedicle screws were placed. The guide plate group achieved a significantly higher rate of perfect screw placement (81.8 vs. 62.3%, P = 0.009) and fewer grade 2 cortical breaches. Operative time, blood loss, and fluoroscopy exposure were significantly reduced in the guide plate group (all P < 0.05). Both groups showed significant postoperative improvements in all clinical scores ( P < 0.05), with no significant intergroup differences at final follow-up. Conclusion Patient-specific 3D-printed guide plates significantly improve screw placement accuracy and reduce operative time, blood loss, and radiation exposure in upper cervical spine surgery, while achieving clinical outcomes comparable to the free-hand technique. This method is a safe and effective alternative for upper cervical pedicle screw fixation.